2018
DOI: 10.1002/pd.5217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience of laboratory follow‐up with noninvasive prenatal testing using cell‐free DNA and positive microdeletion results in 349 cases

Abstract: Overall, this report reveals that while cfDNA analysis will screen for microdeletions, the positive predictive value is low; in our series it is 9.2%. Therefore, the patient should be counseled accordingly. Confirmatory diagnostic microarray studies are imperative because of the high percentage of false positives and the frequent additional abnormalities not delineated by cfDNA analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 21 publications
0
52
1
4
Order By: Relevance
“…However, this task may be difficult because the DR, PPV, and other metrics for 22q11.2 detection in cffDNA are still not clearly defined . The PPV of cffDNA for this microdeletion in all samples varies from 0%, 5%, 9%, 18%, 21% to 96% . In the presence of ultrasound findings, the PPV is higher, reaching 82% to 89% …”
Section: Other Genetic Syndromes Associated With Cardiac Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this task may be difficult because the DR, PPV, and other metrics for 22q11.2 detection in cffDNA are still not clearly defined . The PPV of cffDNA for this microdeletion in all samples varies from 0%, 5%, 9%, 18%, 21% to 96% . In the presence of ultrasound findings, the PPV is higher, reaching 82% to 89% …”
Section: Other Genetic Syndromes Associated With Cardiac Anomaliesmentioning
confidence: 99%
“…66,67 The PPV of cffDNA for this microdeletion in all samples varies from 0%, 5%, 9%, 18%, 21% to 96%. [68][69][70][71][72][73] In the presence of ultrasound findings, the PPV is higher, reaching 82% to 89%. 68,74 Recurrence risk depends on parental status: (…”
Section: Prenatal Ultrasound Findingsmentioning
confidence: 99%
“…However, sub-chromosomal deletion and duplication remain challenging for NIPS owing to the small region of chromosomal abnormality [4]. NIPS coverage has expanded to detecting certain deletion syndromes such as the 22q11.2 deletion syndrome [5], but only few studies have reported the clinical performance of NIPS on duplication detection [6]. Furthermore, there is no evidence to support that NIPS can detect ES, which is a double-segment chromosome duplication of 11q23.3q25 and 22q11.1q11.21.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, PPVs may vary by technology (genome‐wide MPSS‐based and targeted SNP‐based technologies) . In the published studies, the specific clinical context and indications for cfDNA screening are unknown in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%